2020
DOI: 10.1055/s-0040-1720980
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA Methylation Profiles of Hemostatic Genes between Liver Tissue and Peripheral Blood within Individuals

Abstract: DNA methylation has become increasingly recognized in the etiology of complex diseases, including thrombotic disorders. Blood is often collected in epidemiological studies for genotyping and has recently also been used to examine DNA methylation in epigenome-wide association studies. DNA methylation patterns are often tissue-specific, thus, peripheral blood may not accurately reflect the methylation pattern in the tissue of relevance. Here, we collected paired liver and blood samples concurrently from 27 indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Similar approaches using this data have been published recently [32]. Although biomarker discovery that focuses on peripheral whole blood samples is far more feasible than using liver or brain samples, further work is required to understand how DNAm and gene expression differences in the blood might relate to the differences in these tissues of relevance [49,50]. Genetic variations in pharmacokinetic genes have been studied extensively in pharmacogenetic research of antidepressant response and, therefore, are good candidates to study SNP-DNAmgene expression relationships.…”
Section: Discussionmentioning
confidence: 69%
“…Similar approaches using this data have been published recently [32]. Although biomarker discovery that focuses on peripheral whole blood samples is far more feasible than using liver or brain samples, further work is required to understand how DNAm and gene expression differences in the blood might relate to the differences in these tissues of relevance [49,50]. Genetic variations in pharmacokinetic genes have been studied extensively in pharmacogenetic research of antidepressant response and, therefore, are good candidates to study SNP-DNAmgene expression relationships.…”
Section: Discussionmentioning
confidence: 69%
“…We recognize that the use of surrogate tissue (blood cells) to identify changes in DNA methylation of inaccessible target tissues in living patients is a drawback but is the only means of study we have to identify epigenomic biomarkers of growth. Recent studies identified subsets of DMCs that correlate between blood and brain [ 83 ] and blood and liver [ 84 ], but further studies need to be done to generate a map of those sites informative of a wider range of tissues and cell types. Although the population studied was composed of diverse ethnicities, they were largely of white European origin.…”
Section: Limitationsmentioning
confidence: 99%